2019
DOI: 10.21118/apgs.v11i3.5640
|View full text |Cite
|
Sign up to set email alerts
|

Corrupção no Setor Público: Agenda de Pesquisa e Principais Debates a Partir da Literatura Internacional

Abstract: A corrupção no setor público está presente em todos os países do mundo, desde os países desenvolvidos até os mais pobres. Entender como esse fenômeno ocorre em diferentes países é fundamental para o surgimento de mecanismos efetivos de combate à corrupção e o fortalecimento da democracia. Nesse sentido, este estudo buscou responder a seguinte questão: Como o tema da corrupção na Administração Pública vem sendo debatido na literatura internacional?  Para isso utilizou-se análise de conteúdo e revisão sistemátic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 63 publications
0
4
0
6
Order By: Relevance
“…Thus, the focus of the debate is shifted from the State to society and from the market to the public sphere, understood as an environment of public deliberation detached from the structures of power (Filgueiras, 2008;Habermas, 2003;Lubenow, 2012;Mouffe, 2003). Thus, considering that the causes, consequences and solutions to corruption tend to be interconnected (Jain, 2001;Souza et al, 2019), the theoretical perspective called "Pluralist" is presented as an alternative proposal to the dominant currents of thought contained in Table 2.…”
Section: Corruption and The Public Field: In Search Of An Episteme That Reaches The Public Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the focus of the debate is shifted from the State to society and from the market to the public sphere, understood as an environment of public deliberation detached from the structures of power (Filgueiras, 2008;Habermas, 2003;Lubenow, 2012;Mouffe, 2003). Thus, considering that the causes, consequences and solutions to corruption tend to be interconnected (Jain, 2001;Souza et al, 2019), the theoretical perspective called "Pluralist" is presented as an alternative proposal to the dominant currents of thought contained in Table 2.…”
Section: Corruption and The Public Field: In Search Of An Episteme That Reaches The Public Interestmentioning
confidence: 99%
“…In general, the main theoretical perspectives that guide the analysis of corruption are: the legal positivist; the functionalist, which includes the patrimonialism approach; and the economic (Filgueiras, Montandon, Oliveira, & Abreu, 2010;Pinho & Sacramento, 2018); these last two models -functionalist and economic -have dominated Brazilian studies on corruption (Bignotto, 2011;Marani, Brito, Souza, & Brito, 2018;Oliveira, Costa, & Mendes, 2016). Thus, one of the greatest divergences among the authors who have already studied corruption arise from the lack of consensus regarding the exact conceptualization of what is a corrupt action (Biason, 2012;Brei, 1996;Gardiner, 2002;Nye, 1967;Souza, Midlej e Silva, & Gomes, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Corruption generally is associated with the selfish conduct of public servants; nevertheless, Medeiros and Forte (2019) have shown that 'corrupt' describes any individual who ever performs anti-ethical deeds in the public administration, whether or not s/he is a government official. Souza et al (2019a) highlight corruption as the consequence of social inequality, tax evasion, slowdown in economic growth and the resulting lack of resources for investment in a country, especially regarding the education of the masses, who if left unaided must submit to the humiliating conditions that the corruptor imposes on them.…”
Section: Concepts Of Corruptionmentioning
confidence: 99%
“…A presença constante da corrupção e os seus consequentes efeitos sobre a gestão pública são assuntos que têm ganhado cada vez mais destaque no contexto político e social brasileiro. Existente no âmbito público e na seara privada, as suas implicações mais comuns elencadas pela literatura são a desigualdade social, a evasão de receita, a desaceleração do crescimento econômico, o direcionamento de recursos para atividades improdutivas, a instabilidade do regime político e das instituições que representam a base da democracia, bem como a desconfiança sobre as ações públicas (Iquiapaza & Amaral, 2007;Avritzer & Filgueiras, 2011;Power & Taylor, 2011;Souza, Silva & Gomes, 2017). Além dos seus resultados negativos, por ser um fenômeno que acompanha as sociedades desde a antiguidade, ocorrendo nos mais diversos países independentemente da condição econômica dos mesmos e do modelo de governo adotado (Martins, 2008;Filgueiras & Aranha, 2011), o seu controle tornou-se um desafio para o governo brasileiro (Bueno, Brelàz & Salinas, 2016).…”
Section: Introductionunclassified